Population dynamics and environmental degradation in Nepal: An overview - Uprety, Laya Prasad (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 3,037 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v7i0.1110 Occasional Papers in Sociology and Anthropology Vol.7 2001 p.41-64